2015
DOI: 10.1073/pnas.1511308112
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of protein destabilization in live cells

Abstract: Although protein folding and stability have been well explored under simplified conditions in vitro, it is yet unclear how these basic self-organization events are modulated by the crowded interior of live cells. To find out, we use here in-cell NMR to follow at atomic resolution the thermal unfolding of a β-barrel protein inside mammalian and bacterial cells. Challenging the view from in vitro crowding effects, we find that the cells destabilize the protein at 37°C but with a conspicuous twist: While the melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
273
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(293 citation statements)
references
References 65 publications
16
273
0
4
Order By: Relevance
“…1C). T m and ΔG°′ U either decreased or were unchanged compared with buffer (SI Appendix, Tables S1 and S2), consistent with other studies, (13,(15)(16)(17)(18) but inconsistent with previously accepted crowding theory (1,2). ΔC°′ p,U is the same in buffer and in cells (SI Appendix, Table S1).…”
Section: Significancesupporting
confidence: 79%
See 1 more Smart Citation
“…1C). T m and ΔG°′ U either decreased or were unchanged compared with buffer (SI Appendix, Tables S1 and S2), consistent with other studies, (13,(15)(16)(17)(18) but inconsistent with previously accepted crowding theory (1,2). ΔC°′ p,U is the same in buffer and in cells (SI Appendix, Table S1).…”
Section: Significancesupporting
confidence: 79%
“…This approach probably overestimates ΔG°′ U, T (gives the maximum stability, "cells-corrected" in Fig. 1C) because in vitro studies with protein crowders as well as in-cell studies show that destabilizing weak attractive interactions often dominate stabilizing hard-core excluded volume effect (13)(14)(15). We expect the true ΔG°′ U, T lies between the two values.…”
Section: Significancementioning
confidence: 97%
“…inside living cells. 'In-cell' and 'in-lysate' NMR spectroscopy (Danielsson et al 2013(Danielsson et al , 2015Serber et al 2005Serber et al , 2007Smith et al 2013) have developed to a point where new aspects of protein function can be revealed (Banci et al 2013). For instance in a recent study Selenko and co-workers developed an NMR-based methodology that enables quantification of the temporal phosphorylation and de-phosphorylation of short protein segments in cell lysates (Thongwichian et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] To understand the role of other interactions, in recent years, there have been increasing efforts to perform computer simulations with realistic crowder molecules, 4-11 rather than hard-sphere crowders. When analyzing these large systems, a major challenge lies in identifying the main states and dynamical modes, which may not be easily anticipated.…”
Section: Introductionmentioning
confidence: 99%